Java ji shu shou ce : yuan shu di 7 ban = Java in a nutshell: a desktop quick reference, seventh edition - Evans, Benjamin J.; Flanagan, David (O'Reilly jing pin tu shu xi lie hua zhang IT., 2021)
Detailed summary in vernacular field,